The Ideal Educator According to Abd Al-Salām Yāsīn in Forming The Character of Contemporary Students - Wan Muhammad Fariq; Gamal Abdul Nasir Zakaria (Universitas Muhammadiyah Malang, 2024)
Educators are an essential element in the world of education. To become a successful educator, appropriate strategies are needed to convey learning appropriately. A significant figure from Morocco named Abd al-Salām Yāsīn (1928-2012) compiled notes in his book